Exosomal miR‐1255b‐5p targets human telomerase reverse transcriptase in colorectal cancer cells to suppress epithelial‐to‐mesenchymal transition. Issue 10 (19th August 2020) - Zhang, Xue; Bai, Jian; Yin, Hang; Long, Long; Zheng, Zhewen; Wang, Qingqing; Chen, Fengxia; Yu, Xiaoyan; Zhou, Yunfeng
Abstract : Cancer cells undergo epithelial‐to‐mesenchymal transition (EMT) in response to hypoxia. Exosomes produced in tumor microenvironments carry microRNAs (miRNAs) that affect proliferation, metastasis, and EMT. Hypoxic regulation of EMT is associated with telomerase content and stability, but the underlying mechanisms remain unclear. We identified a targeting relationship between tumor‐suppressing miR‐1255b‐5p and human telomerase reverse transcriptase (hTERT) via clinical screening of serum samples in colorectal cancer (CRC) patients. EMT suppression via exosomal miR‐1255b‐5p delivery was investigated by assessing hTERT expression, Wnt/β‐catenin signaling, and telomerase activity. We revealed that hypoxia directly affected exosomal miR‐1255b‐5p content, the delivery of which between CRC cells significantly impacted cell invasion, EMT‐related protein expression, and telomerase stability. Specifically, miR‐1255b‐5p suppressed EMT by inhibiting Wnt/β‐catenin activation via hTERT inhibition. Hypoxia reduced exosomal miR‐1255b‐5p secretion by CRC cells, thereby increasing hTERT expression to enhance EMT and telomerase activity. In a mouse CRC model, hypoxic exosomes containing overexpressed miR‐1255b‐5p attenuated EMT, tumor progression, and liver metastasis. Our results suggest the antitumor role of miR‐1255b‐5p and its involvement in the regulation of hTERT‐mediated EMT. We propose that miRNA‐targeted regulation of telomerase is a promising therapeutic strategy for future CRC treatment. Abstract : Cancer cells undergo epithelial‐to‐mesenchymal transition (EMT) in response to hypoxia. Tumor‐derived exosomes carry microRNAs (miRNA) that affect metastasis and EMT. We identified a targeting relationship between tumor‐derived exosomal miR‐1255b‐5p and human telomerase reverse transcriptase in association with EMT and telomerase stability. We propose miRNA‐targeted regulation of telomerase as a promising strategy for CRC treatment.